Crosstalk Between the MSI Status and Tumor Microenvironment in Colorectal Cancer - Lin, Anqi; Zhang, Jian; Luo, Peng (Frontiers in Immunology, 2020)
Colorectal cancer(CRC) patients have derived clinical benefits from immunotherapy, especially CRC patients with mismatch repair deficiency (dMMR)/microsatellite instability-high(MSI-H), whose sensitivity to immune checkpoint inhibitors(ICIs) is significantly higher than that of patients with microsatellite-stable(MSS)/microsatellite instability-low(MSI-L). Most studies have not systematically evaluated the immune characteristics and immune microenvironments of MSI-H and MSS/MSI-L CRC. We analyzed the relationship between the MSI status and prognosis of ICIs treatment in an immunotherapy cohort. We further used mutation data for the immunotherapy and The Cancer Genome Atlas(TCGA)-CRC[Colon adenocarcinoma(COAD)+rectum adenocarcinoma(READ)] cohorts. For mRNA expression, mutation data analysis of the immune microenvironment and immunogenicity under different MSI status was performed. Compared with MSS/MSI-L CRC, patients with MSI-H CRC significantly benefited from ICIs treatment. We found that MSI-H CRC had more immune cell infiltration, higher expression of immune-related genes and higher immunogenicity than MSS/MSI-L. The MANTIS score used to predict the MSI status was positively correlated with immune cells, immune-related genes, and immunogenicity. In addition, subtype analysis showed that COAD and READ might have different immune microenvironments. MSI-H CRC may have an inflammatory tumor microenvironment and increased sensitivity to ICIs. Unlike those of MSI-H READ, the immune characteristics of MSI-H COAD may be consistent with those of MSI-H CRC.